A 20‐year experience with nocardiosis in solid organ transplant (SOT) recipients in the Southwestern United States: A single‐center study. Issue 4 (9th May 2018) - Majeed, Aneela; Beatty, Norman; Iftikhar, Ahmad; Mushtaq, Adeela; Fisher, Julia; Gaynor, Pryce; Kim, Jeeyong C.; Marquez, Jose L.; Mora, Francisco E.; Georgescu, Anca; Zangeneh, Tirdad
Abstract: Background: Nocardiosis is a life‐threatening opportunistic infection. Solid organ transplant (SOT) recipients are at higher risk (incidence 0.04%‐3.5%) of developing nocardiosis. Rate of nocardiosis in the Southwestern US may be high due to environmental factors. Methods: We performed a retrospective review study on 54 SOT patients diagnosed with Nocardia between 1997 and 2016 at our center. To explore the association of various risk factors with both the development of disseminated disease and mortality, a series of Fisher's exact tests was used. Findings: Incidence of nocardiosis in SOT patients was 2.65%. Fisher's exact tests revealed no association between development of disseminated disease and the following variables: transplant rejection ( P = 1), elevated tacrolimus levels ( P = .4), and CMV viremia ( P = .06). Also, we did not find any association between mortality and the variables we evaluated: type of transplant, transplant rejection, renal failure, disseminated nocardia, and patient's age. Overall mortality and 1‐year mortality were 17% and 11%. Interpretation: Based on our findings, daily 1 DS TMP/SMX prophylaxis did not appear to provide reliable protection against nocardiosis. However, we could not state definitely that TMP/SMX prophylaxis was or wasn't protective because of lack control group. None of the Fisher's exact tests revealed associations between the tested risk factors and either disease dissemination or mortality. This could be due to a true lack of association between the variables in each pair. However, it is also likely that our relatively small sample size limited our power to detect underlying relationships that may be present. Compared with other studies, 1‐year mortality was lower at our institution (11% vs 16%).